2011
DOI: 10.1111/j.1748-7692.2011.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimal similarity in songs suggests limited exchange between humpback whales (Megaptera novaeangliae) in the southern Indian Ocean

Abstract: Comparing humpback whale song from different breeding assemblages can reveal similarities in song due to acoustically interacting males, and therefore indirectly test whether males from different breeding sites are mixing. Northern Hemisphere song comparisons illustrated that whales within ocean basins share similar songs and are subpopulations within a larger population, whereas whales in different ocean basins are isolated populations and therefore do not share songs. During the 2006 breeding season, recordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…Accordingly, duration was variable across themes in the current study, as has been reported in other populations (Payne et al 1983, Darling and Sousa-Lima 2005, Darling et al 2014. Theme 1 was the dominant, or most frequently sung, theme in the 2013 recordings, consistent with previous descriptions of certain themes or phrases as consistently more frequent in production than others (Mercado et al 2003, Darling and Sousa-Lima 2005, Murray et al 2012.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Accordingly, duration was variable across themes in the current study, as has been reported in other populations (Payne et al 1983, Darling and Sousa-Lima 2005, Darling et al 2014. Theme 1 was the dominant, or most frequently sung, theme in the 2013 recordings, consistent with previous descriptions of certain themes or phrases as consistently more frequent in production than others (Mercado et al 2003, Darling and Sousa-Lima 2005, Murray et al 2012.…”
Section: Discussionsupporting
confidence: 86%
“…However, their structure will likely change in subsequent years as the stability of the song changes (Payne et al 1983). Phrases 1-2 and 3-1 were used consistently throughout each song session, which is consistent with what has been cited as transitional in other studies (e.g., Murray et al 2012). Interestingly, a transitional phrase was never noted between themes 2 and 3.…”
Section: Article In Press -Early Viewsupporting
confidence: 89%
See 3 more Smart Citations